SISTEM INFORMASI PENGENDALIAN PIUTANG TAK TERTAGIH PERUSAHAAN MANUFAKTUR: (System Information Control Uncollectible Accounts Receivable in Manufacturing Companies) - Putri Nilasari, Ayunda; Retnosari, Retnosari (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This research was conducted at PT. Hisheng Luggage Accessory Semarang, located at Jl. Gatot Subroto no.02 Kawasan Industri Candi blok 23 no. 6 C Ngaliyan, Semarang. This company engaged in manufacturing. Manual managing receivables seems not efficient. There was no grouping performance of uncollectible accounts, so the obstacles in the settlement of uncollectible accounts still found. The obstacles during grouping the performance of account receivables caused late billing process which also impacted to the payment of uncollectible receivables was not smoothly done. To overcome this problem, the authors build